(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Electrocution injury is due to passage of a substantial electrical current through the tissue, which can cause skin lesions, organ damage, and death. Due to scarcity of typical autopsy findings in electrocution and unclear circumstances of death, many a times cause of death remains undiagnosed. Present study was retrospective, autopsy-oriented study, aimed to study profile of deaths due to fatal electrocution injuries in the Jammu region of union territory of Jammu and Kashmir. During study period 40 cases of electrocution were autopsied at our center. During study period, 1.23% incidence was noted for fatal electrocution deaths. In present study majority of the victims were men (78 %), with a male: female ratio of 3.5:1. Most common age group was 21–30 years (43 %)& upper limbs (58 %) were most common body parts involved. 53 % cases had both entry & exit marks while in 15 % cases no entry or exit marks were noted. Most of the electrocution deaths were accidental, common in males, in the rainy season & most of the deaths were either instantaneous or immediate. Most of the electrocution deaths are preventable in nature and they can be prevented by implementing proper education programs, widespread usage of safety appliances and insulators, keeping electric appliances in child proof cabinets.